Quality of Life in Patients with Acne: A Questionnaire Study - Niraj Parajuli; Bhasker Mohan Meher Kayastha (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Acne vulgaris is a self-limited disorder of the pilosebaceous unit. It is primarily seen in adolescent age group. Acne can present with pleomorphic lesions consisting of comedones, papules, pustules and nodules. Both inflammatory and non-inflammatory acne can produce scarring. It has been found that acne significantly affects self-image and quality of life. Effective treatment results in improvement of quality of life.